Zinc and copper intake and sources in healthy adults living in Bangkok and surrounding districts - Sriwatana Songchitsomboon (2018)
The levels of intake and food sources of zinc and copper in 231 20-80 yr old healthy adults living in Bangkok and surrounding districts were determined. Dietary data from 3-d food records collected and validated at Research Center, Ramathibodi Hospital were analyzed. Levels of zinc and copper intake were compared between sexes and age groups (20-39, 40-59, and 60-80 yr). Mean daily zinc and copper intakes (±SEM) in men were 6.3 ± 0.2 and 1.9 ± 0.1 mg, respectively. Mean daily zinc and copper intakes (±SEM) estimated in women (5.5 ± 0.2 and 1.6 ± 0.1 mg) were significantly lower. Higher zinc and copper intakes were found in the younger (20-39 yr) age group of both sexes. This could be explained by higher density and percentage from animal source of both nutrients. Consumption of various types of meat, fish, egg, and milk accounted for 42 and 22%, and rice, the staple food of Thai people for 9 and 23% of total dietary zinc and copper, respectively.